Kepemilikan Tunggal Badan Hukum Perseroan Terbatas (PT) - Wahyuni, Verti Tri (Faculty of Law, University of Ahmad Dahlan, 2017)
Principally, the responsibility of shareholders based on positive law is limited to the amount of capital deposited. In accordance to Article 3 (1) of Company law number 40 year 2007, it confirms that company shareholder is not subjected to any personal liability for commitments made on behalf of company and shall not be liable for any loss exceeding its shares. The aim of this research is to figure out whether the subjective requirements of limited liability company establishment is absolute or not, and also to figure out how is the legal sanction of sole proprietorsip of a limited company. This research is a juridical normative research. The subjective requirement of limited company establishment is absolute. Limited company may be established by 2 (two) or more shareholders under the notarial deed. The legal sanction of sole proprietorship of a limited company is that the shareholder is personally liable of all company commitments and loss. The shareholders in maximally 6 (six) months after the company is legal under the notarial deed, is obliged to share part of it stock to other shareholders or the company issues a new stock to other. The shareholders are personally responsible if the shareholder is less than 2 (two) persons after 2 (two) months period given by the law.